Complexes of aluminum, iron(III), and gallium(III) chlorides with ethers in synthesis of highly reactive polyisobutylene - Kostjuk, Sergei V. (Journal of the Belarusian State University. Chemistry, 2020)
In this review, the latest achievements in the field of cationic polymerization of isobutylene catalyzed by the complexes of conventional Lewis acids with ethers are presented. The experimental and computational data on the influence of steric structure and basicity of ether used for the preparation of the Lewis acid-ether complex on the catalyst activity and regioselectivity of β-H abstraction are discussed here. Complexes of metal halides with linear (Bu2O) and moderately branched (iPr2O) ethers of moderate basicity (pKa from –4.3 to –5.4) displayed the highest activity and regioselectivity in the cationic polymerization of isobutylene affording highly reactive polyisobutylene (HR PIB) – the key intermediate in the preparation of motor oil and fuel additives. The review is also focusing on the adaptation of the developed catalytic system to the industry, which consists in using non-polar hydrocarbon solvents, high temperatures and monomer concentrations.
Keywords: cationic polymerization; isobutylene; Lewis acids; ethers; highly reactive polyisobutylene